The Approach to the COVID-19 Pandemic in Georgia-A Health Policy Analysis - Ilia Nadareishvili; Ana Zhulina; Aleksandre Tskitishvili; Gvantsa Togonidze; David E. Bloom; Karsten Lunze; Karsten Lunze (Frontiers Media S.A., 2022)
Objectives: This study aimed to analyze key COVID-19 pandemic-related policies and national strategic responses in light of Georgia's political, socioeconomic and cultural backgrounds.Methods: We applied a policy triangle framework for policy analysis, performed document and media content analysis, and described pandemic trends statistically.Results: Early introduction of stringent restrictive measures largely prevented a first wave in March-May 2020. This was communicated as a success story, prompting a public success perception. With unpopular restrictions lifted and hesitancy to embrace evidence-informed policymaking ahead of nationwide parliamentary elections, SARS-CoV-2 infection spread rapidly and was met with an insufficiently coordinated effort. Facing health system capacity saturation an almost complete lockdown was re-introduced in late 2020. Factors as delayed immunization campaign, insufficient coordination and, again, little evidence-informed policymaking eventually led to another devastating COVID-19 wave in summer of 2021.Conclusion: Georgia's pandemic health policy response was adversely impacted by a volatile political environment. National pandemic preparedness and response might benefit from an independent body with appointment procedures and operations shielded from political influences to effectively inform and communicate evidence-based pandemic policy.